Kitab Kuning at the Salafiyah Pesantren in Indonesia: The Dynamics of Online Learning - Makruf Widodo; Maragustam Maragustam; Supriyanto Supriyanto (AL-ISHLAH: Jurnal Pendidikan, 2023)
Documenting the salafiyah pesantren dynamics that have persisted in Indonesia for millennia is a massive undertaking. In today's world, salafiyah Islamic boarding schools and the whirlwind of politics and economics that surrounds them are on the margins. The Covid 19 Pandemic of the 21st century was a major occurrence that disrupted many established systems because of a lack of preparation. It is fascinating to watch the Salafiyah pesantren's dynamic evolve in this context. This study examines how the Salafiyah pesantren in Kebumen, Indonesia, adapted the Kitab Kuning as a means of instruction. Salafiyah Pesantren in Kebumen is the subject of this study using descriptive qualitative research methods which use observation and interview techniques by taking the oldest Pesantren and having a big role in Kebumen. The result of this research is that the Salafiyah Islamic boarding school in Kebumen is trying to make major changes due to the COVID-19 pandemic in the form of a major change in learning media from traditional media to online media, namely using information technology such as mobile phones, which previously was not allowed for students, turning into a necessity for students to have a mobile phone to recite the Kitab Kuning. This dynamic brings changes in behaviour for students, namely the use of health protocols and using social media such as YouTube and WhatsApp as a medium for learning long-distance students.